'I dress in silk and velvet': women, textiles and the textile-text in 1930s Uzbekistan. Issue 1 (2nd January 2022) - Roosien, Claire
ABSTRACT: In the 1930s, luxury textiles such as silk and velvet appeared frequently in agitation and propaganda addressed toward women in Uzbekistan. After examining the cultural and material significance of luxury textiles for Central Asian women before collectivization, this article investigates how luxury textiles were used in the effort to mobilize Central Asian women during the years of collectivization and cottonization ( c. 1929–37). The article concludes with a close reading of several 'textile-texts' produced by Central Asian women, focusing particularly on women's poetry about luxury textiles. The article argues that the discourse of 'silk and velvet' tapped into affective resonances rooted in, among other conditions, the local gift economy, Central Asian women's material conditions, Orientalist discourses and Stakhanovite propaganda. The discourse of silk and velvet thus bolstered hierarchical relations between Central Asian women and the Party–state, while at the same time it generated lateral ties to a public of other Central Asian women. The article relies on research in a variety of archival sources and the Uzbek-language Soviet press, particularly the women's press.